Beyond neoclassical economics: Social process, agency and the maintenance oforder in an Australian illicit drug marketplace - Dwyer, Robyn; Moore, David (Elsevier BV, 2010)
Background: The dominant Australian approaches to understanding illicit drug marketplaces are surveillanceand criminological research. These approaches rely on the elementary neoclassical economic modelof the market which focuses primarily on supply and demand. In this paper, we draw on anthropologicaland sociological research to develop an alternative framework for understanding Australian illicit drugmarketplaces that emphasises their constituent processes.Methods: The paper draws ontwoyears of ethnographic researchamongheroin user/sellers of Vietnameseethnicity in an Australian heroin marketplace.Results: Trade and barter were key modes of exchange in this marketplace. We identified active negotiationand bargaining over price on the basis of social relationships, with dealers and customers activelyworking to develop and maintain such ties. Dealers set price collectively and this was shaped by moraland cultural elements such as notions of a ‘fair’ price. Social processes and relations as well as sharedcultural expectations helped to generate trust and maintain order in the marketplace.Conclusion: Our ethnographic research suggests that the dominant Australian approaches to the study ofillicit drug markets, with their reliance on the elementary neoclassical economic market model, ignorethe social processes and social relations through which such sites are made and remade. Nor do they adequatelycapture the complex character of the subjects who act within these sites. If we are to expand ourunderstanding of illicit drug markets and marketplaces in Australia,wemust look beyond the conceptionsoffered by surveillance and criminological approaches.© 2010 Elsevier B.V. All rights reserved.